Avaliação de estações climáticas virtuais e do modelo ORYZAv3 para a região de arroz tropical irrigado - Menezes, Caio Teodoro (2021)
In Brazil, there are two main rice producing regions, subtropical and tropical. In the subtropical region, production is more stable whereas in the tropical region it is still unstable. This difference is caused by environmental and social factors. One way to improve this situation is by using crop models since they can capture environmental and management interactions. This study aims to assess, first, the gridded weather database (GWD) used as an input in crop modelling. Verifying the feasibility of DailyGridded and NASA/POWER datasets in ORYZA (v3) crop model, using upland rice in the tropical region considering sandy and clay soil conditions. In the second phase, we calibrate and validate two rice crops for the tropical region so their feasibility in studies on tropical region could be checked. In the first chapter, it is observed that both GWD are more reliable only when there is no drought stress, due to uncertainties created by GWD-based rainfall. This error is higher in sandy soil conditions. In the second chapter, two rice crops, BRS Catiana and IRGA 424, are calibrated using data from two trials carried out in Goianira-GO, showing a good agreement in this step. On the validation step, we observe a yield bias as a function of latitude, with a tendency to overestimate results in places nearby the calibration area and underestimate them on locations further north. For those reasons these calibrated crops are not indicated to be used in studies regarding the tropical region.